Sliders and Backsliders: Toronto's Sunday Tobogganing Controversy of 1912 - Homel, Gene (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1981)
A conflict in Toronto municipal politics in 1912 centred on the question of whether the civic government should allow its toboggan slides in the parks to be used on Sunday. A well-organized and influential Sabbatarian movement forced the issue, and while labour and business leaders mobilized to protect Sunday recreation, the Sabbatarians convinced City Council to close the slides on the Lord's Day. This article examines the persistence of Sabbatarian belief as well as the increase of sentiment favourable to a more secularized view of Sunday recreation.